Anterior maxillary defect reconstruction with a staged bilateral rotated palatal graft - Jung, Gyu-Un (Korean Academy of Periodontology, 2014)
PURPOSE: In the anterior maxilla, hard and soft tissue augmentations are sometimes required to meet esthetic and functional demands. In such cases, primary soft tissue closure after bone grafting procedures is indispensable for a successful outcome. This report describes a simple method for soft tissue coverage of a guided bone regeneration (GBR) site using the double-rotated palatal subepithelial connective tissue graft (RPSCTG) technique for a maxillary anterior defect. METHODS: We present a 60-year-old man with a defect in the anterior maxilla requiring hard and soft tissue augmentations. The bone graft materials were filled above the alveolar defect and a titanium-reinforced nonresorbable membrane was placed to cover the graft materials. We used the RPSCTG technique to achieve primary soft tissue closure over the graft materials and the barrier membrane. Additional soft tissue augmentation using a contralateral RPSCTG and membrane removal were simultaneously performed 7 weeks after the stage 1 surgery to establish more abundant soft tissue architecture. RESULTS: Flap necrosis occurred after the stage 1 surgery. Signs of infection or suppuration were not observed in the donor or recipient sites after the stage 2 surgery. These procedures enhanced the alveolar ridge volume, increased the amount of keratinized tissue, and improved the esthetic profile for restorative treatment. CONCLUSIONS: The use of RPSCTG could assist the soft tissue closure of the GBR sites because it provides sufficient soft tissue thickness, an ample vascular supply, protection of anatomical structures, and patient comfort. The treatment outcome was acceptable, despite membrane exposure, and the RPSCTG allowed for vitalization and harmonization with the recipient tissue. GRAPHICAL ABSTRACT: [Image: see text]